Oral morphine protocol evaluation for the treatment of vaso-occlusive crisis in paediatric sickle cell patients. Issue 1 (31st May 2018) - Paquin, Hugo; D. Trottier, Evelyne; Robitaille, Nancy; Pastore, Yves; Dore Bergeron, Marie-Joelle; Bailey, Benoit
Abstract: Background: Vaso-occlusive crisis (VOC) is one of the most frequent causes of emergency visit and admission in children with sickle cell disease (SCD). Objectives: This study aimed to evaluate whether the implementation of a protocol promoting the use of oral morphine as a primary intervention has led to improved care of SCD. Methods: We performed a retrospective chart review of patients with SCD who presented to the emergency department (ED) and hematology outpatient clinic (HOC) with VOC, in the year pre and postimplementation of the protocol. The primary outcome was the hospitalization rate. Results: The protocol resulted in a significant 43% reduction of hospitalization rate (95% confidence interval [CI] −53.0, 26.5). Results also showed a 35% increase in the use of oral morphine as first-line opiate treatment (95% CI 17.9, 45.2), a 28% increase in the use of pain scales (95% CI 17.3, 43.2) and a 30% net increase in patients eventually not requiring intravenous (IV) line placement (95% CI 16.0, 39.9). While we did observe an overall decrease in length of stay in ED of -55 min (95% CI −100.6, −12.0), there was a nonsignificant decrease of 7 minutes (95% CI −26, 3) in the opiate administration time. Conclusions: This study validates the use of our oral morphine protocol for the treatment of VOC by significantly reducing the admission rate and decreasing the number of IVs.